Cytosolic Triosephosphate Isomerase from Arabidopsis thaliana Is Reversibly Modified by Glutathione on Cysteines 127 and 218 - Dumont, Sébastien; Bykova, Natalia V.; Pelletier, Guillaume; Dorion, Sonia; Rivoal, Jean (Frontiers in Plant Science, 2016)
In plant cells, an increase in cellular oxidants can have multiple effects, including the promotion of mixed disulfide bonds between glutathione and some proteins (S-glutathionylation). The present study focuses on the cytosolic isoform of the glycolytic enzyme triosephosphate isomerase (cTPI) from Arabidopsis thaliana and its reversible modification by glutathione. We used purified recombinant cTPI to demonstrate the enzyme sensitivity to inhibition by N-ethylmaleimide, hydrogen peroxide and diamide. Treatment of cTPI with diamide in the presence of reduced glutathione (GSH) led to a virtually complete inhibition of its enzymatic activity by S-glutathionylation. Recombinant cTPI was also sensitive to the oxidized form of glutathione (GSSG) in the micromolar range. Activity of cTPI was restored after reversion of S-glutathionylation by two purified recombinant A. thaliana cytosolic glutaredoxins (GRXs). GRXs-mediated deglutathionylation of cTPI was dependent on a GSH-regenerating system. Analysis of cTPI by mass spectrometry after S-glutathionylation by GSSG revealed that two Cys residues (Cys127 and Cys218) were modified by glutathione. The role of these two residues was assessed using site-directed mutagenesis. Mutation of Cys127 and Cys218 to Ser separately or together caused different levels of decrease in enzyme activity, loss of stability, as well as alteration of intrinsic fluorescence, underlining the importance of these Cys residues in protein conformation. Comparison of wild type and mutant proteins modified with biotinyl glutathione ethyl ester (BioGEE) showed partial binding with single mutants and total loss of binding with the double mutant, demonstrating that both Cys residues were significantly S-glutathionylated. cTPI modification with BioGEE was reversed using DTT. Our study provides the first identification of the amino acid residues involved in cTPI S-glutathionylation and supports the hypothesis that this reversible modification could be part of an oxidative stress response pathway.